STRATEGI DISTRIBUSI PRODUK TEH SIAP SAJI - Sally Wiedjarnarko; Anas Miftah Fauzi; Meika Syahbana Rusli (School of Business, Bogor Agricultural University (SB-IPB), 2015)
Freshbrew Mels Beverages is a small-sized packaged tea beverage company. The brand product is